Binary Opposition Found in the Characterization of Lemony Snicket’s Ersatz Elevator Novel - Sheila Larasati; Riana Permatasari (J-Lalite: Journal of English Studies, 2023)
This study aims to analyze the characterization of the characters in Lemony Snicket’s Ersatz Elevator novel. The found characterizations were then later categorized and sorted so that it could be contrasted and formed into a binary opposition. Binary opposition is chosen to analyze the novel because of the children's literature’s nature of contrasting the characters. The primary data were taken from the novel in the form of dialogues and narrations while the secondary data were taken from the various sources that were deemed to support the study. The data found in the novel were then identified, classified, and reduced. This study was finished with two results. The first result is the characterization found in characters are; greedy, grateful, indifferent, caring, coward, and brave. The second result deals with the binary opposition. The pairs found in the novel are greedy – grateful, indifferent – caring, and coward – brave. After thorough interpretation and analysis, the study shows that there is a power imbalance between in between the adult and the children characters as they have opposite traits with each other along with their responsibilities as their respected roles. The power imbalance shown in the characters are made more prominent by how the children are portrayed to be the hero by the author while the adults are portrayed to be reckless.